ผลกระทบของข้อมูลบนป้ายจราจรสลับข้อความและเส้นสีต่อการตัดสินใจในการเลือกเส้นทางของผู้ขับขี่ - สมชาย วิกิจไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Variable Message Sign (VMS) is a technology for displaying traffic information such as traffic situation, traffic problem, suggestion for alternate routes, and road incidents. The VMS can help motorists plan and make better decision for their travel. The objective of this study is to evaluate motorist’s awareness and decision regarding text message and color-coded traffic information on the VMS display in order to analyze potential factors that could affect route choice decision on Bangkok expressway. Samples are taken from motorists who drive from Din Daeng to Rama IX Bridge by means of questionnaire surveys based on traffic information from text messages and color-code traffic information. Results from ordered discrete modeling reveal that changing various message types on the VMS has no effect on driver’s route choice. However, the color-coded traffic information can significantly affect driver’s decision. Others significant variables include the derived congestion index, driving frequency, and awareness of traffic information prior to the trip. The findings from this study could help developing appropriate content for VMS display that is useful, correct, and more consistent to motorist’s demand.